(3GdJMbjb aj TQGA GdQbjbs
(3ChdgG (B:s
(3GdMeO ddg HLejY eMGeOg adjS Ndb ef GdCMjG fYdeg ef Pi MLGR hdG TGe hdGjef GdGhge TQcGA ai ahGVd s
(3BNQgG (B:s
(3Gdae aeUfY GdYhO GdQWH hGdcSaQI hGdeVeVI HGdNeQ heG GdhQO hGdYhO GdefbhY GdCSfGf s
(3HChdg agQSs
(3LYd GdeDda cJGHg gPG HGSe Gdedc GdUGdM CMeO Hf GdeXaQ ZGRi GHf GdSdWGf UdGM GdOjf jhSa Hf CjhH Hf TGPi hGdUGY GdePchQ cGf UGMH YjfJGH hdO SfI (B600 (3J Sfg (B651s
(3Ydjg GdYOjO ef GdJedcGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdSjGSI hGdGLJeGYs